Comparison of the effects of piezoelectric and calcium ionophore activation on fertilization and blastulation rates of sibling oocytes - Funda Göde; Ibrahim Pala; Fatma Yıldırım; Zahra Abdi (Gynecological Endocrinology)
To determine rates of fertilization, good-quality day 3 embryos, and blastocyst progression in sibling oocytes of the same patients undergoing piezo and calcium ionophore (CaI) activation. The retrospective cohort study included couples undergoing assisted reproductive treatment in 2023–2024 for primary infertility with a history of low fertilization rates (<30%), low blastulation rates (<20%), or male factor infertility such as teratozoospermia at the Izmir University of Economics Medical Point Hospital IVF Center. Sibling oocytes from each patient were randomly assigned to piezoelectric or CaI activation. The fertilization rate, number of degenerated embryos, number of abnormally fertilized eggs, number of day 3 grade 1 embryos, and blastocyst counts were compared among the sibling oocytes. In total, 1,105 MII sibling oocytes from 76 patients were included. Piezoelectric activation was applied to 575 MII oocytes, while CaI activation was applied to 530 MII oocytes. There was no significant difference between groups according to the activation method in the fertilization rate (piezo, 0.74% ± 0.22%; CaI, 0.68% ± 0.26%, p = 0.12), degeneration rate (piezo, 0.04% ± 0.13%; CaI, 0.02% ± 0.06%, p = 0.452), day 3 grade 1 embryo rate (piezo, 0.59% ± 0.33%; CaI, 0.54% ± 0.35%, p = 0.34), or blastocyst rate (piezo, 0.49% ± 0.33%; CaI, 0.43% ± 0.34%, p = 0.28) of sibling oocytes. Both piezoelectric and CaI activation yielded comparable results in terms of oocyte activation, with similar fertilization and blastulation rates.